Mengukur Ruh dan Raga: Peran Evaluasi Holistik PAI dalam Kurikulum Merdeka - Sangadah, Siti; Dewi, Rachma Rusdiana; Ridho, Ahmad Rosyid (TSAQOFAH, 2026)
Evaluation in Islamic Religious Education (PAI) often remains focused solely on measuring the cognitive domain, even though the primary goal of PAI is the formation of character and the holistic internalization of religious values. This study aimed to analyze the strategic role of holistic evaluation and the comprehensive evaluation models relevant to improving the quality of PAI, particularly in the context of the Kurikulum Merdeka. The method employed was library research with content analysis of various recent literature on PAI evaluation and curriculum development. The findings show that PAI evaluation should ideally be multidimensional, integrating the cognitive, affective, and psychomotor domains in a unified manner. Synergy among the CIPP Model (for systemic evaluation), the Kirkpatrick Model (for measuring behavioral change), and Tyler’s Goal Attainment Model (for assessing the achievement of objectives) is required to ensure the effectiveness and relevance of PAI programs. This study concludes that evaluation functions not only as a tool for measuring learning outcomes but also as a strategic instrument for curriculum development, the strengthening of instructional practice, and the assurance of sustainable quality in Islamic education within the framework of Kurikulum Merdeka.